Protein intake and nitrogen balance in male non-active adolescents and soccer players - Boisseau, N.; Le Creff, C.; Loyens, M.; Poortmans, J. R. (European Journal of Applied Physiology, 2002)
Recommendations for the requirements for protein intake amount usually to 0.8-1.0 g·kg-1 body mass·day-1 in adolescents without any reference to the undertaking of acute exercise or to the training status. The present investigation intended to determine the nitrogen balance and protein intake in 8 healthy male non-active adolescents and 11 adolescent soccer players, both groups aged about 15 years. An assessment of nutrient intake was obtained by analysing 7 day food records collected by a questionnaire. Nitrogen excretion rate was determined and nitrogen balance was calculated from the mean daily protein intake and the urinary excretion. The results showed that the nutritional status of the two groups was similar. Nevertheless, we found that their diets were quite inappropriate in terms of the intakes of carbohydrate, some minerals (zinc, calcium, magnesium), vitamins (A, B6, D) and fibre. A positive nitrogen balance was observed from a mean protein intake of 1.57 g·kg-1 body mass·day-1 in these adolescents, whether they were non-active or athletes. Thus, the present investigation indicated that the growth and development in non-active adolescents and in adolescent soccer-players give rise to a need for a higher protein intake than is usually recommended. However, the higher protein requirements did not seem to be related only to the increased energy expenditure imposed by the exercise training in the soccer-player group.